Organic geochemical characterisation of shallow marine Cretaceous formations from Yola Sub-basin, Northern Benue Trough, NE Nigeria. (May 2016) - Sarki Yandoka, Babangida M.; Abdullah, Wan Hasiah; Abubakar, M.B.; Hakimi, Mohammed Hail; Jauro, Aliyu; Adegoke, Adebanji Kayode
Abstract: The shallow marine shales of the Cretaceous formations namely Yolde, Dukul, Jessu, Sekuliye and Numanha ranging in age from Cenomanian to Coniacian within the Yola Sub-basin in the Northern Benue Trough, northeastern Nigeria were analysed to provide an overview on their hydrocarbon generation potential. This study is based on pyrolysis analysis, total organic carbon content (TOC), extractable organic matter (EOM), biomarker distributions and measured vitrinite reflectance. The present-day TOC contents range between 0.24 and 0.71 wt. % and Hydrogen Index (HI) values between 8.7 and 113 mg HC/g TOC with Type III/IV kerogens. Based on the present-day kerogen typing, the shale sediments are expected to generate mainly gas. Biomarker compositions indicates deposition in a marine environment under suboxic conditions with prevalent contribution of aquatic organic matter and a signiﬁcant amount of terrigenous organic matter input. Organic matter that is dominated by marine components contains kerogens of Type II and Type II-III. This study shows that the organic matter has been affected by volcanic intrusion and consequently, have reached post-mature stage of oil generation. These higher thermal maturities levels are consistent with the vitrinite reﬂectance ranging from 0.85 to 2.35 Ro % and high Tmax ( 440–508 °C) values as supported by biomarker maturity ratios. Based on this study, a high prospect for major gas and minor oil generation potential is anticipated from the shallow marine Cretaceous formations from Yola Sub-basin. Highlights: The marine Cretaceous shales are organically lean and contain Type III/IV kerogens. Based on present-day kerogen typing, the shales are expected to generate mainly gas. Biomarkers indicates deposition in marine environment under suboxic conditions. Aquatic organic matter and a signiﬁcant amount of terrigenous organic matter input. The organic matter has been affected by volcanic intrusion based on thermal maturity.